Sistem Informasi Persediaan Sebagai Alat Untuk Meningkatkan Penjualan Barang Berbasis Client Server - Eni Endaryati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
Increasing competition in business competition, especially in companies engaged in the trading sector, requires every business actor to be quick and responsive in handling or responding to the condition of his sales, this is intended so that the company's sales results continue to increase And one of the main keys in sales is the inventory of goods, inventory goods or inventory are goods that can usually be found in closed warehouses, fields, open warehouses, or other storage places, either in the form of raw materials for semi-finished goods, goods for operational purposes, or goods for the needs of a project. By managing goods properly, it will certainly make it easier to find and get information for available goods. And to manage this information, a computer-based inventory information system is needed, which is expected to increase sales volume. The information system created will assist companies in finding or processing data on available goods, processing the entry and exit of goods, as well as knowing information on suppliers